Coccolithophores as potential marine resource for sustainable aquaculture - Vicente, Bernardo (2019)
Coccolithus braarudii (holococcolith) and Emiliana huxleyi (heterococcolith) were isolated from Portuguese coastal waters and domesticated under laboratory conditions with the objective of providing strains with high potential for the production of high value products for aquaculture and biotechnology. The growth patterns and photophysiology of the two species were investigated under controlled conditions, (19±1°C, 12:12 Light: Dark, 115 µmol photons m-2 s-1) using pulse amplitude modulated fluorometry (PAM), and the different growth phases characterized by flow cytometry (cell size, complexity, chlorophyll a autofluorescence and lipid content). The biochemical and nutritional profile of the studied species was assessed by elemental analyses, gravimetric quantification of total lipids and the fatty acid profile determined by gas chromatography coupled with mass spectrometry. The growth rate of C. braarudii was on average 69.5% higher (0.76d-1) when compared with E. huxleyi (0.44d-1) (P=0.005). Results from biochemical analyses revealed that this strain of C. braarudii has high protein and lipid content, 34.6% and 22.1% of total dry weight, respectively. The fatty acid (FA) profile was mainly composed of ω-3 PUFA, 64.1% total FA, with high levels of DHA and EPA. E. huxleyi revealed lower (P<0.001) protein and lipid contents and a fatty acid profile rich in DHA but poor in EPA. Finding alternative sources to ω-3 PUFA from wild fish is currently a major challenge for aquaculture. Given the cell size, high growth rate and nutritional quality, C. braarudii is a promising candidate for microalgae-based diets in aquaculture, particularly of larval stages, thus contributing to sustainable aquaculture practices.